The recipe book and the construction of female domestic identity: a historical inquiry - Carew, Nina (University of Cape Town, 2020)
This thesis explores how familiar objects such as the homely recipe book hold our affection and shape our personal worlds. It takes its inspiration from a body of literature that only recently has explored in detail our relationship to mundane objects, subjecting these objects - and our feelings about them - to a serious scrutiny. The thesis is concerned with a material culture that takes us into domestic space, and to the objects within it to which we attach importance. Specifically, the inquiry explores the cultural mores surrounding the practice of cooking and writing food. It considers the interplay between public and private, male and female, self and other and the significance of the domestic space in each case. It asks how the culture of the recipe book helps shape female domestic identity, that is, the personae of women within the home, and as wives and mothers, as opposed to their public personae. This thesis studies the (until-recently) under-researched yet broad field - previously regarded as both too trivial and too formulaic to merit study - of homely recipe books. It considers the large collection of historic manuscripts of this genre available at the National Library of South Africa, in particular the collection of Louis C Leipoldt, and it regards these as part of a continuum with my own mother's recipe book. An important leitmotif of the study is the evolution of the recipe book from manuscript to printed, and from single copy to mass-produced text. On the one hand using recipe books as historical sources for the study of food and material culture, this study is also concerned with the affective impact of these texts, and more specifically what they say about the individuals and societies that made them. A central theme of the study is the role played in women's lives by the collecting and archiving of recipes through hand-written texts. My purpose is twofold: first, to bring these hidden histories to light, opening the kitchen door to the lives of ordinary women through their private writings; and second, to explore why the practice of writing food continues to be relevant into the present. I trace how homely recipe books are both exercises in personal authority as well as material traces of women's internal worlds and archives of the communities in which they exist. This study ultimately sees the return of the personalised recipe book as a route back to a positive and affirming female domestic identity, through a practice which is both therapeutic and self-actualising and which, through the act of archiving, brings together both past and present.